PENGARUH PENYULUHAN DENGAN MEDIA PERMAINAN ULAR TANGGA TERHADAP PENGETAHUAN TENTANG BUAH DAN SAYUR PADA SISWA MTs-S ALMANAR KECAMATAN HAMPARAN PERAK - Irma Handayani; Zulhaida Lubis; Evawany Y Aritonang (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ABSTRACT           Fruit and vegetables are very beneficial for the body, but school-aged children seldom consume them even though it is the period for school-aged children to growth so that consuming healthful foods is very important for their growth and development. Nutrition counseling by using snake ladder game can be used to cope with that problem. The objective of this research was to find out the influence of snake ladder game on knowledge of fruits and vegetables in the students of MTs-S Almanar, Hamparan Perak.           The research used quasi experimental method with pretest-posttest control group design and one type treatment. The experimental group consisted of the students of MTs-S Almanar and the control group consisted of 16 students who had gotten intervention of snake ladder game three times, and 16 students without intervention. The data were collected by using questionnaires and analyzed by using mann whitney test.          The result of the research showed that there was the influence of nutrition counseling by using snake ladder game on increasing knowledge (p=0.0001), in the students of MTs-S Almanar, Hamparan Perak.           It is recommended that the management of MTs-S Almanar and MTs-Sabila, Hamparan Perak perform development, direct, and motivate nutrition counseling by using snake ladder game. The management of the Puskesmas should actively and routinely counseling nutrition about fruit and vegetables at school, especially at MTs-S Almanar and MTs-S Sabila, Hamparan Perak. Keywords: Snake Ladder Game, Knowledge , Fruit, Vegetables